InteSmart Stationary and Bookstore / Norzalina Taslim - Taslim, Norzalina; Abdullah, Mohd. Najib; Janaludin, Noor Salfarina; Mohd. Zaid, Izwain; Ahmad Zaki, Amiza Shazwani; Sallehuddin, Noor Fadhilah (2005)
InteSmart Stationary and Bookstore is a partnership business manager opened by six people who act as a general manager, assistant general manager, marketing executive, operation executive, account clerk and general clerk. InteSmart Stationary Bookstore is set up to sell the stationary, books, news paper, magazine and novels to the customer. The target markets for our business are students, teachers, and lecturers, working people, parents, teenagers and children.